Molecular medical parasitology - Marr, J. Joseph (James Joseph); Nilsen, Timothy W.; Komuniecki, Richard (Academic Press, 2003)
A valuable, new source, Molecular Medical Parasitology is the only text of its kind -- one that applies broad concepts and current scientific advances from both molecular biology and biochemistry to the study of parasitic organisms. An internationally renowned team of scientists and physicians places parasites in their broad biological contexts while still emphasizing the specifics that differentiate these organisms. Not only will researchers and faculty in parasitology find this an indispensable guide, physicians will benefit from the thorough coverage molecular biology and biochemistry's current influences on treatment and management of parasitic diseases. Key Features * Features the most up-to-date scientific methods behind the medical management of parasitic diseases * Applies the most current synthesis of molecular biology and biochemistry to parasitic organisms * Contains many informative figures and clear illustrations.